Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.7759/cureus.17283
|View full text |Cite
|
Sign up to set email alerts
|

Determination of COVID-19 Vaccine Hesitancy Among University Students

Abstract: IntroductionWith the sudden outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-COV-2), vaccines appear to be the most efficient measure in combating spread. However, vaccines are only effective if a community collectively uptakes vaccination. This approach is growing increasingly difficult with the emergence of 'Vaccine Hesitancy.' This paper aims to determine the association between university curricula and the degree of hesitancy for the COVID-19 vaccine. MethodsThe online questionnaire assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
(22 reference statements)
2
9
0
Order By: Relevance
“…Additionally, our study reports that medical students tend to read scientific journals more readily than nonmedical students; a similar pattern was found in previous research [21]. They were also less likely to believe that vaccines offer complete protection against COVID-19, which is in line with the current understanding of how the vaccine works -the COVID-19 vaccine offers protection against only the most severe manifestations of the infection.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Additionally, our study reports that medical students tend to read scientific journals more readily than nonmedical students; a similar pattern was found in previous research [21]. They were also less likely to believe that vaccines offer complete protection against COVID-19, which is in line with the current understanding of how the vaccine works -the COVID-19 vaccine offers protection against only the most severe manifestations of the infection.…”
Section: Discussionsupporting
confidence: 89%
“…One possible explanation for the disparity in vaccination rates is that young people believe they are not at risk of COVID-19 complications [19]. The most common reasons for vaccine hesitancy were found to be concerns over the side effects and concerns over the efficacy of the vaccines, which is consistent with previous research in the UAE, and among other university students worldwide [10,[20][21][22], but in contrast to a low-income country like that of Afghanistan, where a study found that the ma- jor reason for hesitancy among the general population for taking the COVID-19 vaccine was their belief that the COVID-19 vaccine, which will be provided for low-income countries, might be of low quality [23]. Similarly, in Ethiopia, people who live in rural areas were more likely to be hesitant to take the vaccine [24].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The majority of non-medical students showed hesitancy towards obtaining COVID-19 vaccines compared to medical students who were more willing, largely owing to their knowledge and understanding of vaccines [ 15 ]. In Uganda COVID-19 vaccine acceptability among medical students was 37.3% and vaccine hesitancy was 30.7% [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…As well as, their senses of collective responsibility as future members of the health care team toward their own health and the whole community health. In the same line, a study done by (Sadaqat et al, 2021) about determinants of vaccine hesitancy among university students reported that non-medical students had higher rate of vaccine hesitancy against the COVID-19 vaccine, as compared to medical students. However, (Barello et al, 2020) in a study about vaccine hesitancy among college students in Italy, found no difference between medical and nonmedical students in relation to uptake of vaccines.…”
Section: Discussionmentioning
confidence: 93%